Self-directed learning readiness, academic self-efficacy, and problem-solving ability among nursing students in Cebu - Yao, Johnny J. Jr
The ability to solve problems is a professional skill that enables nursing students to execute nursing interventions when they go into their duty. This is essential when they become future nurses. To enhance nursing students' problem-solving abilities, educators have been trying to develop appropriate teaching strategies. This study examined the relationship between problem solving ability, self-directed learning readiness, and academic self-efficacy among nursing students. This study utilized a descriptive correlational study and recruited 170 nursing students in a private higher education institution in Cebu. Standardized questionnaires were distributed, and data were analyzed using descriptive and inferential statistics. Results show that there is a significant indirect association between self-directed learning readiness and problem-solving ability (r = -.525, p < .001). There is a significant direct association between self-directed learning readiness and academic self-efficacy (r = .549, p < .001). Lastly, there is a significant indirect association between academic self-efficacy and problem-solving ability (r = -.505, p < .001). The findings are able to substantiate the assumptions of the study that self-directed learning readiness, academic self-efficacy, and problem-solving ability of students have relationships with each other. Thus, students who are self-directed learners and are confident with their abilities of success in school tasks are able to solve complex problems or issues.